2013
DOI: 10.2355/isijinternational.53.2142
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Non-metallic Inclusion Formation and Modification and Their Deformation during Compact Strip Production (CSP) Process for Aluminum-Killed Steel

Abstract: The formation and modification of non-metallic inclusions for Al-killed steel during Compact Strip Production Process (CSP Process) was studied by industrial experiments. The thermodynamics for the formation of Al2O3, MgO·Al2O3 spinel, various calcium aluminates and CaS bearing inclusion were analyzed with the help of calculation software FactSage. It is found that the oxygen activity in liquid steel during LF (Ladle Furnace) refining is confirmed to be determined by the equilibrium between dissolved Al and Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 14 publications
4
33
0
1
Order By: Relevance
“…As for Ref. 17), it was presumed that Ca content might be similar to ours by considering the slag compositions despite no descriptions regarding Ca content in the middle stage of LF refining.…”
Section: Composition Evolution During Lf Refining Processsupporting
confidence: 50%
See 4 more Smart Citations
“…As for Ref. 17), it was presumed that Ca content might be similar to ours by considering the slag compositions despite no descriptions regarding Ca content in the middle stage of LF refining.…”
Section: Composition Evolution During Lf Refining Processsupporting
confidence: 50%
“…It was reported that both MgO·Al 2 O 3 and the CaO-Al 2 O 3 system inclusions were detected in the refining stages of Al-killed steels. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] According to the report, MgO·Al 2 O 3 inclusions have the potential to cause nozzle clogging due to its high sinterability because they are stable with a solid state at the steelmaking temperatures.…”
Section: Factors To Determine Inclusion Compositions In Molten Steel mentioning
confidence: 99%
See 3 more Smart Citations